Blended learning versus face-to-face learning in an undergraduate nursing health assessment course: a quasi-experimental study - Berga, Keri-Ann; Vadnais, Elisha; Nelson, Jody; Johnston, Sharon; Buro, Karen; Hu, Rui (My University, 2021)
Background: Blended learning, which integrates face-to-face and online instruction, is increasingly being adopted. A gap remains in the literature related to blended learning, self-efficacy, knowledge and perceptions in undergraduate nursing. Objectives: To investigate outcomes of self-efficacy, knowledge and perceptions related to the implementation of a newly blended course. Design: This was a quasi-experimental pre-post test design. Setting: This study was conducted at an undergraduate university in Alberta, Canada. Participants: A total of 217 second-year undergraduate nursing students participated and 187 participants completed all study components. Methods: A convenience sampling method was used. Data were collected at the start and end of the semesters. Data were analyzed using descriptive and inferential statistics using R(3.4.3) and R-Studio(1.1.423). Results: There were no significant differences in self-efficacy scores between groups or in the pre-post surveys (p > 0.100) over time. There was no significant difference in knowledge between the blended online and face-to-face groups (p > 0.100). For students in the blended course, perceptions of the online learning environment were positive. Conclusion: Blended learning has the potential to foster innovative and flexible learning opportunities. This study supports continued use and evaluation of blended learning as a pedagogical approach.
Keywords: blended learning; nursing students; teaching methods; baccalaureate nursing education; undergraduate; self-efficacy